Orientation of carbon fiber precursors from 1‐butyl‐3‐metylimidazoluim chloride cellulose solutions. Issue 2 (22nd June 2012) - Sammons, Rhea J.; Collier, John R.; Rials, Timothy G.; Spruiell, Joseph E.; Petrovan, Simioan
Abstract Cellulose/1‐butyl‐3‐methylimidazolium chloride ([Bmim]Cl) solutions were wet spun at varied concentrations, temperatures and draw down ratios using a semi‐hyperbolically converging die to produce fibers that were highly oriented and highly crystalline. The orientation number (NOR) and the Herman's orientation factor (fH) were compared with the fiber crystallinity. The analysis of the results indicates that the spinning parameters had a significant effect on the fiber properties, especially the orientation factor as well as the orientation number. Therefore, to spin cellulose fibers that would be suitable for carbon fiber precursors, the spinning parameters are a high concentration solution at approximately 90°C and at a medium draw ratio. This would yield fibers with a high orientation number. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013